Beyond Remittances: Migration as Moral Economy, Symbolic Practice, and Identity Negotiation among Returned Migrants in Cilacap Regency - Suyanto Suyanto; Arido Laksono; Tari Purwanti (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
This study examines migration and remittance practices among returnees to Cilacap Regency, moving beyond dominant economic perspectives and focusing on their cultural and symbolic dimensions. Based on in-depth interviews with ten returnees, the study explores how migration is embedded in moral obligations, social recognition, and identity negotiations. The findings indicate that migration is primarily understood as a moral responsibility towards family, where remittances function as obligatory expressions of reciprocity rather than voluntary financial transfers. At the same time, remittances operate as visible markers of success that shape social status and generate new forms of inequality through processes of comparison and recognition. Furthermore, the return experience highlights ongoing identity negotiations, as migrants navigate expectations, gender roles, and shifting positions within their communities. Remittances are not simply economic resources but symbolic practices that sustain relationships, generate meaning, and shape social life. Thus, this study extends existing migration scholarship by demonstrating that economic outcomes cannot be fully understood without examining the underlying cultural logics. While previous research, particularly by Hein de Haas, has emphasized the conditional economic impacts of migration, this study complements that perspective by highlighting the moral, symbolic, and experiential dimensions of remittance practices